The Effect of Propolis Extract on MDA Levels (Malondialdehyde) and Sperm Quality on Epididimis (Experimental Study on Wistar Strain Male Rats Exposed to Kretek Cigarettes) - Hoesada, Ivan; Nasihun, Taufiqurrahman; Isradji, Israhnanto (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Cigarette smoke exposure increase free radicals and effecting male infertility. Propolis is commonly used as supplement to increase antioxidant levels. Objectives: To prove the effect of propolis extract to MDA level and spermatozoa quality on epididymis due to cigarette smokes. Methods: Experimental research post test only control group design using 30 male rats Wistar Strain, 8 weeks old, weighed 200 – 250 gram, randomly divided into 5 groups. K-1 (normal), do not received propolis and cigarettes smoke; K-2 (negative control) exposed to cigarettes smokes 4 buds/ day, did not received propolis; K-3, K-4, and K-5, apart from cigarrete smokes 4 buds/day each were given propolis with 2.9 mg, 5.4 mg, dan 8.3 mg/200g body weight/day for 21 days. On the 22nd day, rats were sacrificed, sperms were extracted from cauda epididymis, and then examined for MDA and sperm quality. Statistical analysis used was one way ANOVA, continued with post hoc LSD with significance level of p<0,05. Results: ANOVA test on MDA level and sperm quality between groups showed significant difference of, p = 0.005. Post hoc test indicated that MDA on K-5 (1,12) is significantly lower compare to K-2 (5,89), p = 0,001. As well as consentration, motility and morphology (spermatozoa quality) which indicated that K-5 (49.32, 64.15, 36.34) is significantly higher compared to K-2 (22.62, 27.27, 21.39), each with p value of p = 0.001.Conclusion: extract propolis 8,3 mg/day for 21 days is proven to increase spermatozoa quality and lower the MDA level on male rats wistar strains’ epididimis exposed to cigarettes smoke.